Analisis Bentuk dan Proporsi Patung Monumen Veteran di Gedung Yudha Bhakti DPD Legiun Veteran Republik Indonesia di Kota Medan - Afini Afini; Tetty Mirwa (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to find out the shape and proportion of monument statues of veterans in the building yudha bhakti DPD legion of veterans of the Republic of Indonesia in the city of Medan. The problem is focused on the shape and structure of the proportions of the sculpture that are less in accordance with anatomical theory. Data collection procedures are carried out through observations, interviews and documentation studies. The data is observed by deciphering and clarifying based on the anatomical form of the statue. The research method used in this research is descriptive qualitative research, because it is a research that seeks to break down, explain and describe all data obtained from research. The results showed that veteran monument statues still have shortcomings, both in terms of shape and proportion, but this does not reduce the implied meaning of the monument statues of veterans of the Republic of Indonesia in the city of Medan.